2020
DOI: 10.3390/antiox10010003
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Oatmeal on Exercise-Induced Reactive Oxygen Species Production Following High-Intensity Interval Training in Women: A Randomized Controlled Trial

Abstract: High-intensity interval training (HIIT) has been demonstrated to increase the generation of reactive oxygen species (ROS). Therefore, strategies to mitigate excessive ROS productions could be useful to reduce the negative consequences of oxidative damage for health, as well as for physical, performances. The aim of this study was to investigate the acute effects of pre-exercise oatmeal consumption on exercise-induced ROS generation in young, healthy women. Thirty-four participants were randomly allocated in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…This present study discovered waist-hip ratio had no significant difference although reduction was shown in the subjects after the 4-week of intervention between pre and post tests (p>0.05). This finding was similar with several previous studies also found there was not significant reduction in waist-hip ratio between pre and post test intervention of oat consumption [30][31][32][33]. Xue et al reported that waist-hip ratio did not decrease significantly with consumption of oat bran although blood pressure reduced significantly [30].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This present study discovered waist-hip ratio had no significant difference although reduction was shown in the subjects after the 4-week of intervention between pre and post tests (p>0.05). This finding was similar with several previous studies also found there was not significant reduction in waist-hip ratio between pre and post test intervention of oat consumption [30][31][32][33]. Xue et al reported that waist-hip ratio did not decrease significantly with consumption of oat bran although blood pressure reduced significantly [30].…”
Section: Resultssupporting
confidence: 90%
“…(20221) discovered that oat contain Avenanthramide (AVA) which was an antioxidants agent that able to reduce reactive oxygen species resulting from exercise [33]. Avenanthramide (AVA) in oats was able to reduce blood inflammatory markers and reactive oxygen species, activation of NF-κB mononuclear cells and increased antioxidant capacity [34][35].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, measurements cannot be taken as an accurate representation of in vivo antioxidant capacity [ 259 ]. An additional direct measurement technique for assessing ROS generation ex vivo is electron paramagnetic resonance [ 182 , 260 ], while the majority of studies use indirect markers of oxidative stress as surrogate markers [ 261 ]. These factors along with the pharmacokinetics of different dietary supplements must be considered when planning the blood-collection schedule of a study [ 257 ].…”
Section: Oxidative Stress and Athletic Antioxidant Statusmentioning
confidence: 99%
“…Taherkhani et al (2021) also reported that the exercises oriented to enhance physical performance and achievement significantly increase free radical formation. Additionally, studies also revealed that high-intensity exercise (Zeng et al, 2020) and anaerobic exercise substantially improve free radical formation (Tofas et al, 2019). Linearly, ultra-marathon running also expands the formation of free radicals, but it is not equal to the increase of antioxidants (Thirupathi et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%